Innovative integration of sustainable urban development in Meru, Ipoh (Meru Garden Village) - Radzi, Muhammad Eidlan Hakimi; Mat Radi, Syasya Balqis; Rosli, Nurdina Samirah; Abdullah, Lizawati (2024)
Meru Garden Village, is a development project that emphasizes sustainable urban planning and green building technology that is developed in Meru, Ipoh. The main goal of this development project is to create a shopping center that is energy efficient, sustainable, clean and relaxing in addition to being environmentally friendly. There are several innovations that have been proposed for this project, namely the use of a QR code system for the entire location of the outlet mall building, green landscaping, a transparent lake with clear pebbles supported by water filtration system, green roof technology and rainwater harvesting technology for domestic purposes. These innovations are designed to minimize maintenance cost reduction, improve energy efficiency, convenience for visitors and create an aesthetically neutral environment. With these diversity of innovations, Meru Garden Village can function as an outlet mall that can meet the criteria and wishes of visitors in addition to being able to offer attractive packages.